Mikroklima archívů - Onderek, Aleš (Vysoké učení technické v Brně. Fakulta stavební, 2018)
Diplomová práce se zabývá uchováváním inventářů v depozitářích. Dále se zabývá návrhem vzduchotechnického systému archívu. V poslední části diplomové práce je proveden experiment zabývající se zkoumáním vnitřního mikroklimatu depozitáře.

The thesis focuses on the way inventories are stored in depositories. Later on, it develops a project of the air-conditioning system in the archive. The last part of the thesis deals with an experiment which examines the interior environment of the depository.
Environment of archives
Keywords: Archív; depozitář; inventář; relativní vlhkost; teplota; měrná vlhkost; klimatizace; vzducho-technická jednotka; Archives; depository; inventory; relative humidity; temperature; specific humidity; air han-dling unit